Exploring Batik Semarangan as a medium to develop intercultural communication awareness and global competence - Dukut, Ekawati Marhaenny (citeus, 2023)
People doing work from home are mostly depending on what the internet has to offer for communication. Because people want to make good use of the Internet for communication, such information is available in English as a global language. One of the advantages of having ready information in English is that local cultural products can now have better chances to compete globally with products from other cultures. One of those products is Indonesia’s Batik Semarangan, which is produced in Semarang, the capital city of Central Java. Through studying the motifs found in Batik Semarangan, an intercultural communication awareness of rich hybrid culture can be achieved. To ensure awareness, a group of English Department’s literature students was trained to do library and field research on Batik Semarangan. By applying Roland Barthes’ semiotics, students were encouraged to explore the hidden reasons for the unique choice of Batik Semarangan motifs. By doing this activity, not only were the students equipped to be more critical in researching local products but the lecturer has also helped preserve and elevate Batik as a traditional heritage that has global potentiality.